Strategi Dakwah Nabi Musa: The Da'wah Strategy of Prophet Musa - Agusman, Agusman; Samsuddin, Samsuddin (Litera Academica Publishing, 2024)
Prophet Musa AS’s da’wah strategy is a classic example of an effective approach in various historical and social contexts. This study analyzes Prophet Musa’s da’wah strategies in dealing with Fir'aun, the Children of Israel, and Samiri to identify effective methods for conveying divine messages and their relevance today. The methodology includes literature analysis from the Qur'an, exegesis, and secondary sources on da’wah strategies. Findings show that Prophet Musa used miracles and assertiveness in confronting Fir'aun, applied education and guidance for the Children of Israel, and enforced laws against Samiri. His strategies emphasize the importance of assertiveness, patience, and contextual adaptation in da’wah. Lessons from these strategies can help contemporary da’ees and leaders design more adaptive and relevant da’wah approaches, utilizing modern technology and social media while considering current social and cultural contexts